2013
DOI: 10.6061/clinics/2013(04)08
|View full text |Cite
|
Sign up to set email alerts
|

Protective response in renal transplantation: no clinical or molecular differences between open and laparoscopic donor nephrectomy

Abstract: OBJECTIVE:Prolonged warm ischemia time and increased intra-abdominal pressure caused by pneumoperitoneum during a laparoscopic donor nephrectomy could enhance renal ischemia reperfusion injury. For this reason, laparoscopic donor nephrectomy may be associated with a slower graft function recovery. However, an adequate protective response may balance the ischemia reperfusion damage. This study investigated whether laparoscopic donor nephrectomy modified the protective response of renal tissue during kidney tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…These injuries indicate that pneumoperitoneum and surgical manipulation causes acute tubular necrosis accompanied by peritubular capillary congestion. 42 Although the duration of pneumoperitoneum was relatively short, this study results showed the presence of endothelial and renal tubular markers to the inflammation were higher, especially when standard or high pressure pneumoperitoneum was used. The use of low pressure pneumoperitoneum may have attenuated these systemic and vascular inflammatory responses (Figure 7).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…These injuries indicate that pneumoperitoneum and surgical manipulation causes acute tubular necrosis accompanied by peritubular capillary congestion. 42 Although the duration of pneumoperitoneum was relatively short, this study results showed the presence of endothelial and renal tubular markers to the inflammation were higher, especially when standard or high pressure pneumoperitoneum was used. The use of low pressure pneumoperitoneum may have attenuated these systemic and vascular inflammatory responses (Figure 7).…”
Section: Discussionmentioning
confidence: 63%
“…39,40 There is an increase in VGEF-mRNA expression at laparoscopic sites as a response to the injured tissue. [40][41][42] When inflammation occurs, IL-6 and activated syndecan-1 stimulate the synthesis of VEGF-A molecules and its binding to its regulator VEGFR-2 on the glomerular and peritubular capillaries endothelial cells, as well as tubular epithelial cells. 39,40 Increasing plasma sVEGFR-2 level and VEGFR-2 expression on tubular epithelial cells to the adjacent endothelial cells depends on the extent of inflammation that results in an increased endothelial permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 There is an increase in VGEF-mRNA expression at laparoscopic sites as a response to the injured tissue. [40][41][42] In a normal human kidney, VEGFR-2 is expressed on glomerular and peritubular capillaries endothelial cells, as well as tubular epithelial cells at a low degree. 39,40 When inflammation occurs, IL-6 and activated syndecan-1 in the endothelial cells shedding and the release of VEGFR-2 are believed to have renal-protective roles.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, acute tubular necrosis was observed in 44% of open nephrectomy and 45% of laparoscopic patients, and 54% of renal biopsy specimens taken from laparoscopic nephrectomy showed subcapsular cortical injury. These injuries indicate that pneumoperitoneum and laparoscopic surgical manipulation causes acute tubular necrosis accompanied by peritubular capillary congestion 42. Despite the absence of syndecan-1 from the glomerular and peritubular endothelial glycocalyx, it was found in the membrane of the proximal and distal tubules and was important for renal tubular cell survival during inflammation.…”
mentioning
confidence: 99%